2019
DOI: 10.1038/s41420-019-0163-9
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of HB-EGF binding peptides and their functional characterization in ovarian cancer cell lines

Abstract: Ovarian cancer is one of the most frequent causes of cancer death among all gynecologic cancers. Though standard therapy often results in temporary clinical remission, most patients suffer from recurrence and metastasis of ovarian cancer, which highlights the need for developing new therapeutic agents targeting specific molecules. Previous studies have demonstrated that the native ligand of epidermal growth factor receptor (EGFR) and ErbB4, heparin-binding EGF-like growth factor (HB-EGF), plays a critical role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…As the full picture of miRNA-mRNA networks has yet to be accomplished [56], the results presented here may be helpful to find key regulators of OC network. In line with our findings, all 6 miRNAs (hsa-miR-126-3p, hsa-miR-223-3p, hsa-miR-23a-5p, hsa-miR-27a-5p, hsa-miR-486-5p, and hsa-miR-506-3p) and 8 mRNAs (ATF3, CH25H, EMP1, HBB, HBEGF, NAMPT, POSTN, and PROCR) have been previously shown to play an essential role in ovarian carcinogenesis with respect to different aspects such as OS, histological subtype, clinical stage, chemoresistance, or treatment [19,20,27,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. We reported previously that hsa-miR-23a-5p, hsa-miR-27a-5p, and hsa-miR-126-3p, were significantly associated with OS in the same EOC cohort (p < 0.01, univariate Cox regression analysis) [27].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…As the full picture of miRNA-mRNA networks has yet to be accomplished [56], the results presented here may be helpful to find key regulators of OC network. In line with our findings, all 6 miRNAs (hsa-miR-126-3p, hsa-miR-223-3p, hsa-miR-23a-5p, hsa-miR-27a-5p, hsa-miR-486-5p, and hsa-miR-506-3p) and 8 mRNAs (ATF3, CH25H, EMP1, HBB, HBEGF, NAMPT, POSTN, and PROCR) have been previously shown to play an essential role in ovarian carcinogenesis with respect to different aspects such as OS, histological subtype, clinical stage, chemoresistance, or treatment [19,20,27,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. We reported previously that hsa-miR-23a-5p, hsa-miR-27a-5p, and hsa-miR-126-3p, were significantly associated with OS in the same EOC cohort (p < 0.01, univariate Cox regression analysis) [27].…”
Section: Plos Onementioning
confidence: 99%
“…Vert et al demonstrated that activating transcription factor 3 (ATF3) in OC cell lines has a crucial role for antitumor activity and to strengthen the antiviral properties of an RNA-damaging drug, Onconase [67]. The inhibition of heparin-binding epidermal growth factor-like growth factor (HBEGF) has been proposed as a novel therapeutic strategy for patients with paclitaxel-resistant OC [68,69]. Overexpression of nicotinamide phosphoribosyltransferase (NAMPT) has been described across a broad range of solid tumors including ovarian, colorectal, breast, gastric, prostate, and endometrial carcinomas in addition with melanoma, gliomas, and astrocytomas indicating that inhibition of NAMPT may be used as a cancer treatment strategy [70].…”
Section: Plos Onementioning
confidence: 99%
“…Similar to NGF and other neurotrophins, HB-EGF is synthesized in a premature transmembrane form (pro-HB-EGF) before it is cleaved by numerous metalloproteinases (MMP3, MMP9, ADM9, ADAM10, ADAM12, ADAM17) into its mature, soluble form (215). While the membrane anchored pro-HB-EGF functions as juxtacrine growth factor and receptor for diphtheria toxin in some species, soluble HB-EGF has recently been described to modulate cell migration, differentiation, and inflammatory functions in multiple cell types (216)(217)(218)(219)(220)(221)(222). In addition, HB-EGF enhances neurogenesis in models of ischemic injury and promotes the survival of dopaminergic neurons (223,224) (Figure 2).…”
Section: Hb-egfmentioning
confidence: 99%
“…The phage displayed random peptide library identification is an effective way of detecting peptides that can bind and control target molecular behaviors. This method has been practiced in identifying receptor-bound bioactive peptides [ 166 ], disease-specific antigen mimics [ 166 , 167 ], cell-specific peptides, non-protein-bound peptides [ 168 ], or organ-specific peptides [ 169 ], as well as in the designing of peptide-mediated drug delivery systems [ 165 ]. Consequently, analysis for bioactive peptides applying phage display technology is an advantageous approach that can be used in basic research.…”
Section: Production Of Opioid Peptides From Food Proteinsmentioning
confidence: 99%